Enamel Matrix Derivative in Propylene Glycol Alginate for Treatment of Infrabony Defects With or Without Systemic Doxycycline: 12‐ and 24‐Month Results. Issue 5 (1st May 2014) - Eickholz, Peter; Röllke, Lasse; Schacher, Beate; Wohlfeil, Martin; Dannewitz, Bettina; Kaltschmitt, Jens; Krieger, Jörg K.; Krigar, Diana M.; Reitmeir, Peter; Kim, Ti‐Sun
Abstract : Background: This aim of this study is to compare regenerative therapy of infrabony defects with and without administration of post‐surgical systemic doxycycline (DOXY) 12 and 24 months after therapy. Methods: In each of 57 patients, one infrabony defect (depth ≥4 mm) was treated regeneratively using enamel matrix derivative at two centers (Frankfurt am Main and Heidelberg). By random assignment, patients received either 200 mg DOXY per day or placebo (PLAC) for 7 days after surgery. Twelve and 24 months after surgery, clinical parameters (probing depths [PDs] and vertical clinical attachment level [CAL‐V]) and standardized radiographs were obtained. Missing data were managed according to the last observation carried forward. Results: Data of 57 patients (DOXY: 28; PLAC: 29) were analyzed (26 males and 31 females; mean age: 52 ± 10.2 years; 13 smokers). In both groups, significant ( P <0.01) PD reduction (DOXY: 3.7 ± 2.2 mm; PLAC: 3.4 ± 1.7 mm), CAL‐V gain (DOXY: 2.7 ± 1.9 mm; PLAC: 3.0 ± 1.9 mm), and bone fill (DOXY: 1.6 ± 2.7 mm; PLAC: 1.8 ± 3.0 mm) were observed 24 months after surgery. However, the differences between both groups failed to be statistically significant (PD: P = 0.574; CAL‐V: P = 0.696; bone fill: P = 0.318). Conclusions: Systemic DOXY, 200 mg/day for 7 days, after regenerative therapy of infrabony defects did not result in better PD reduction, CAL‐V gain, or radiographic bone fill compared with PLAC 12 and 24 months after surgery, which may be attributable to low power and, thus, random chance.